Development of Comic Maker on Narrative Text for Eleven Grade Students of SMA Negeri 5 Pekanbaru - Putra, Bramudia Sakra; Niah, Siti; Ardiya, Ardiya (FKIP - Universitas Riau, 2024)
Narrative text is a type of writing that tells a story to entertain readers or listener. Its main goal is to entertain people with various experiences. Additionally, language features in narrative texts include using descriptive words like adjectives and adverbs, action verbs, and being written from either a first or third-person perspective. Comics are among the various educational tools featuring illustrated stories. Their primary function in education is to inspire student motivation. Unlike other tools, comics can stand alone and improve learning outcomes even when used differently. Traditionally printed on paper, comics are now increasingly digital, accessible via computers, tablets, or smartphones. Digital comics offer an innovative and creative learning medium expected to enhance student understanding of subjects. This study aimed to develop comic media for learning media, as well as to assess the students’ response toward the media. Analysis of student responses using the Percentage of Total Response Formula developed by Riduwan (2015) indicates that students have shown a positive reaction to the developed